Regional integration and growth spillovers: Is Africa an economic space? - Abdoulaye Seck; Founty Alassane Fall; Khadidiatou Aidara (Journal of African Trade, 2020)
Market integration is often associated with economic growth spillovers, to the extent that strengthened trade linkages would make economic growth in one country an opportunity for growth to its partners. This paper uses a spatial dynamic panel data approach to analyze the extent to which Africa and its major regional groupings have been able to generate shared growth. The results indicate that the continent as a whole is indeed a spatially integrated economic zone. Although of a weak proportion compared to advanced economies, the contemporaneous spatial growth effect is associated with strong growth convergence and a large rate of return to physical capital. The results also suggest that space has more to do with bilateral trade than geographical distance, and point to a great deal of heterogeneity: the positive growth spillover effect in regional groupings such as South African Development Authority, Common Market for Eastern and Southern African, and Economic Community of West African States, which happen to register larger intraregional trade shares, contrast with the absence of such an effect in Economic Community of Central African States and Arab Maghreb Union, two blocks which have achieved little in terms of economic integration. These results should be a welcome addition to the debate over the opportunity of the proposed continent-wide free trade area and its ability to foster inclusive and sustainable economic growth and development for African economies.
Keywords: C23; F15; 330; Regional integration; trade; growth spillovers; Africa; spatial dynamic panel; Regionale Wirtschaftsintegration; Regionales Wachstum; Spillover-Effekt; Afrika